THE INFLUENCE OF INFLATION AND RETURN ON INVESTMENT (ROI) WITH THE DU PONT METHOD SYSTEM OF STOCK RETURN PT. LIPPO KARAWACI DURING THE YEAR 2010-2019 - Yulandri, Elsa; Hartati, Neneng (Finansha: Journal of Sharia Financial Management, 2020)
Abstract In investment transactions in the capital market, an investor will expect a higher level of investment invested. In order for the expected results to be appropriate, it is necessary to analyze the financial statements of a company with fundamental and technical analysis. This article aims to show the effect of inflation and ROI with the du pont system method on the stock return of PT. Lippo Karawaci, Tbk. Inflation is an increase in the price of goods and services in general over a long period of time. Meanwhile, the ROI du pont system is a ratio that measures how good the total assets can generate investment. This article also uses descriptive methods and quantitative approaches, namely to describe the research results presented in numerical form. The data in this article is secondary data taken from the financial statements of PT. Lippo Karawaci, Tbk, and supported by a library and documentation studio, which is processed statistically and quantitatively. The results of the study concluded that both partially and simultaneously inflation and ROI with the Du Pont System method did not have a significant effect on stock returns of PT. Lippo Karawaci. The second variable contribution is only 31%, meaning that it is 69% stock return, other factors are outside this study. Keywords: Inflation, ROI with the Du Pont System Method, Stock Return. Abstrak Dalam transaksi investasi di pasar modal, seorang investor akan mengharapkan tingkat pengembalian yang tinggi atas investasi yang ditanamkan. Agar hasil yang diharapkan sesuai maka perlu dilakukan analisis terhadap laporan keuangan suatu perusahaan dengan analisis fundamental dan teknikal. Artikel ini bertujuan untuk menguji pengaruh inflasi dan ROI dengan metode du pont system terhadap return saham PT. Lippo Karawaci, Tbk. Inflasi merupakan kenaikan harga barang dan jasa secara umum dalam jangka waktu yang panjang. Sedangkan ROI du pont system merupakan rasio yang mengukur seberapa besar total aset dapat menghasilkan pengembalian investasi. Artikel ini juga menggunakan metode deskriptif dan pendekatan kuantitatif, yakni untuk mendeskripsikan hasil penelitian yang datanya disajikan dalam bentuk numerik. Data pada artikel ini merupakan data sekunder yang diambil dari laporan keuangan PT. Lippo Karawaci, Tbk dan didukung dengan studi kepustakaan dan dokumentasi, yang diolah scara statistik dan kuantitatif. Hasil penelitian ini menyimpulkan bahwa baik secara parsial dan simultan inflasi dan ROI dengan dengan metode Du Pont System tidak memiliki pengaruh yang signifikan terhadap return saham PT. Lippo Karawaci. Kontribusi kedua variabel hanya 31%, artinya sebesar 69% return saham dipengaruhi oleh faktor-faktor lain diluar penelitian ini. Kata kunci: Inflasi, ROI dengan Metode Du Pont System, Return Saham